2013
DOI: 10.1371/journal.pone.0074182
|View full text |Cite
|
Sign up to set email alerts
|

Very Early Passive Cycling Exercise in Mechanically Ventilated Critically Ill Patients: Physiological and Safety Aspects - A Case Series

Abstract: IntroductionEarly mobilization can be performed in critically ill patients and improves outcomes. A daily cycling exercise started from day 5 after ICU admission is feasible and can enhance functional capacity after hospital discharge. In the present study we verified the physiological changes and safety of an earlier cycling intervention (< 72 hrs of mechanical ventilation) in critical ill patients.MethodsNineteen hemodynamically stable and deeply sedated patients within the first 72 hrs of mechanical ventila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 22 publications
6
68
1
7
Order By: Relevance
“…For those In-bed cycling is a promising technology to enhance rehabilitation in critically ill patients. [9] To-date, 6 ICU studies have reported cycling in a total of 173 patients [16,[20][21][22][23][24] with more than 600 sessions reported. [16,[21][22][23][24] Of these 6 reports, there were 3 case series, [21][22][23] 1 case control study, [24] and 2 randomized clinical trials (RCTs), [16,20] with sample sizes varying from 16 [24] to 90 [16] enrolled patients.…”
Section: Discussionmentioning
confidence: 99%
“…For those In-bed cycling is a promising technology to enhance rehabilitation in critically ill patients. [9] To-date, 6 ICU studies have reported cycling in a total of 173 patients [16,[20][21][22][23][24] with more than 600 sessions reported. [16,[21][22][23][24] Of these 6 reports, there were 3 case series, [21][22][23] 1 case control study, [24] and 2 randomized clinical trials (RCTs), [16,20] with sample sizes varying from 16 [24] to 90 [16] enrolled patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, similar metabolic changes are observed during many routine intensive care activities, such as physical examination, bathing and patient re-positioning (Weissman et al, 1984), and hence the changes may be well tolerated unless there are pre-existing poor cardiac reserves. In contrast, a more recent report demonstrated no significant changes in cardiac function or metabolic activity during 20 minutes of passive cycling, even in patients requiring vasoactive agents (Camargo Pires-Neto et al, 2013). Passive limb movements also seem to be well tolerated in critically-ill patients with raised intracranial pressure (Brimioulle et al, 1997).…”
Section: Progression Of Rehabilitation Interventionsmentioning
confidence: 93%
“…Some authors suggest that passive limb movements as part of a programme of early rehabilitation are insufficient to preserve muscle strength and that mobilisation out of bed is essential for improved patient outcomes (Hodgson et al, 2013). However, the current body of evidence (Brimioulle et al, 1997;Burtin et al, 2009;Camargo Pires-Neto et al, 2013;Freitas et al, 2012;Griffiths et al, 1995;Pinheiro and Christofoletti, 2012;Savi et al, 2010;Schweickert et al, 2009;Silva et al, 2010;Wiles and Stiller, 2010) supports the concept that passive limb movements not only are safely tolerated in critically-ill sedated patients even on vasoactive support (when early mobilisation out of bed is not indicated) but when delivered using continuous passive movement devices may be beneficial to prevent muscle wasting, reduce systemic inflammation and improve patient outcomes (Burtin et al, 2009). Mobilisation out of bed may be safely initiated in the intubated and mechanically ventilated patient (Bailey et al, 2007;Burtin et al, 2009;Morris et al, 2008;Schweickert et al, 2009), however this may only be feasible in patients with single organ failure such as respiratory failure and in patients with sufficient muscle strength.…”
Section: Facilitation Of Rehabilitation Of the Intubated And Mechanicmentioning
confidence: 99%
“…Pires-Neto et al 30 assessed hemodynamic, respiratory, and metabolic effects of early use of the cycle ergometer in critically ill patients. The authors used the equipment in the first 72 hours of mechanical ventilation in 19 patients and did not observe significant changes in the variables analyzed.…”
Section: Discussionmentioning
confidence: 99%